2018
DOI: 10.3389/fmolb.2018.00079
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of Gene Expression Profiles Controlled by hnRNP Q and hnRNP R, Two Closely Related Human RNA Binding Proteins Implicated in mRNA Processing Mechanisms

Abstract: Heteregeneous ribonucleoproteins (hnRNPs) are a family of RNA-binding proteins that take part in all processes that involve mRNA maturation. As a consequence, alterations of their homeostasis may lead to many complex pathological disorders, such as neurodegeneration and cancer. For many of these proteins, however, their exact function and cellular targets are still not very well known. Here, we focused the attention on two hnRNP family members, hnRNP Q and hnRNP R, that we previously found affecting TDP-43 act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 76 publications
(100 reference statements)
2
19
0
Order By: Relevance
“…Our analysis found a significant enrichment of proteins involved in RNA and mRNA processing, including hnRNP R and hnRNP U. We validated the biochemical interactions of KPNA7 with hnRNP R and hnRNP U, and we also determined the importance of putative mono-and bipartite NLS sequences in these hnRNPs 42,43 . We found that the E344Q substitution in KPNA7 reduced binding and transport mediated by the NLS in hnRNP R and hnRNP U.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our analysis found a significant enrichment of proteins involved in RNA and mRNA processing, including hnRNP R and hnRNP U. We validated the biochemical interactions of KPNA7 with hnRNP R and hnRNP U, and we also determined the importance of putative mono-and bipartite NLS sequences in these hnRNPs 42,43 . We found that the E344Q substitution in KPNA7 reduced binding and transport mediated by the NLS in hnRNP R and hnRNP U.…”
Section: Discussionsupporting
confidence: 60%
“…Based on protein sequence analysis and its similarity to the closely related hnRNP Q, hnRNP R was proposed to contain both a monopartite NLS (mNLS, a.a. 412-418) and a bipartite NLS (bNLS, a.a. 565-589) ( Fig. 4a) 42,43 . The necessity and sufficiency of these NLSs in hnRNP R, however, have not been tested.…”
Section: Identification Of Kpna7 Interacting Proteins In Neuronsmentioning
confidence: 99%
“…HNRNPR modulates cap-independent translation rates in the cytosol by linking target mRNA IRESs (Geuens et al 2016). Finally, HNRNPR and SRSF1 have been reported in mRNA stabilization (Lemaire et al 2002;Sun et al 2011;Cappelli et al 2018) and could play this role for c-Myc transcripts as well.…”
Section: New C-myc Rbps Identified By Hypr-msmentioning
confidence: 96%
“…Of note, there has been a little emphasis from any study in determining the potentially different roles of the separate isoforms of these proteins. Given that it appears different R and Q isoforms may serve distinct, non-redundant cellular functions [23], it will be important to establish whether they also play different roles in disease pathogenesis.…”
Section: Hnrnp R and Hnrnp Qmentioning
confidence: 99%
“…Further functions of hnRNP Q include the post-transcriptional modulation of circadian clock gene mRNAs levels [ 94 , 95 ], morphological development of neuromuscular junctions [ 194 ] and the exosomal sorting of specific micro RNAs [ 72 ]. Both hnRNP R and Q have been identified as potentially important regulators of neuronal homeostasis and cellular pathways associated with neurodegeneration [ 23 ].…”
Section: The Hnrnp Familymentioning
confidence: 99%